ANALISIS DAYA SAING AGRIBISNIS RUMPUT LAUT DI KABUPATEN LOMBOK TIMUR - Fadli Fadli; Rachmat Pambudy; Harianto Harianto (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2017)
Seaweed is a potential commodity to be cultivated in improving people's welfare. Seaweed development is the right step in increasing competitive advantage to the comparative advantage owned by east lombok regency. Increasing the competitiveness of seaweed is not only focused on improving the competitiveness of its products, but the most important is the effort in improving the competitiveness of seaweed farmers in the village of Seriwe East Lombok regency. The purpose of this reseach are (1) to analyze and measure the competitiveness of seaweed in East Lombok Regency; (2) to analyze the impact government policy on improving seaweed competitiveness in East Lombok Regency; and (3) to analyze the sensitivity price change of the input and output on seaweed competitiveness in East Lombok Regency. The study was designed as a descriptive survey which includes qualitative and quantitative data. Analisis tools in this study is Policy Analysis Matrix (PAM). Based on the results of PAM analysis, seaweed have competitiveness when cultivate seaweed through raft systems, basic offshore systems, and longline systems.